Employing Service Learning in Community-University Partnership Program to Develop Local MSMEs in Bungo and Tejo Regencies - Novita, Mona; Ismail, M. Syukri; Solihin, Muhammad; Asman, Muhammad (UI Scholars Hub, 2003)
This paper illustrates the implementation of a community project developed based on a partnership between the community and the local university in Bungo and Tebo Regencies. The project aims to develop the local micro, small, and medium enterprises (MSMEs) as a strategic step to increase the regional economy, taking the form of a so- called Community–University Partnership Program in Bungo and Tebo Regencies. The Community–University Partnership methodology employs the Service Learning (SL) method to increase MSME actors’ competence in terms of financial literacy, product packaging, and marketing. The effectiveness of the SL-based Community–University Partnership Program was measured using a quantitative survey approach through a questionnaire instrument on 28 MSMEs in Bungo and Tebo Regencies. The program showed a positive impact, in which the MSMEs actors benefited from the SL-based Community–University Partnership Program. The continuation of the SL-based Community–University Partnership Program arguably improves MSME’s development and enhances the regional economy to establish financial independence for citizens.